Thai Civil Registration and Vital Statistics and Unique Identification Number Systems for Universal Health Coverage : A Case Study - Pannarunothai, Supasit (World Bank, Washington, DC, 2019)
The Thai civil registration (CR) system was established two centuries ago. Over the past four decades, the system has changed from a manual, paper-based registration system to a centralized, electronic, online system. A unique identification number (UIN) system was implemented in 1982, along with a computerized CR database system. The Thai citizen identification card has evolved along with the two systems from a paper card to an integrated circuit–chip smart card. All provincial-, district-, and municipality-level registration offices are linked online to the central CR system database. Thailand’s vital statistics (VS) system has improved since 1996, when the CR system began feeding electronic birth and death data directly into the VS management system. VS reports are now up to date, of good quality, and available for use by any agency that needs them. Thailand declared its universal health coverage (UHC) policy in 2001. Health insurance coverage was expanded to all Thais through the Universal Coverage Scheme. The use of UINs and CR databases has enabled and facilitated rapid enrollment of beneficiaries and improved the beneficiary registries of all three of the country’s major insurance plans. All Thais are entitled to coverage from one of these plans. The use of UINs and personal demographic information from the CR system significantly improved the quality of health care information and provider payment systems. Misuse of UINs and personal information in CR is threatening the integrity of the UIN and central CR databases. New initiatives by the Thai government, such as the National Digital Identification Platform project, are ongoing to expand e-government and private services and to prevent the misuse of personal information and personal identity challenges.